Development of next-generation formulation against Fusarium oxysporum and unraveling bioactive antifungal metabolites of biocontrol agents - Monika Jangir (Nature Portfolio, 2021)
Abstract Biocontrol agents serve as a sustainable means of controlling wilt caused by the widespread plant pathogen, Fusarium oxysporum f. sp. lycopersici. The present study aimed to develop water dispersible granules (WDG) using response surface methodology (RSM) for Bacillus subtilis MTCC 2274 and Trichoderma harzianum MTCC 3928, and to compare their antifungal efficacy with other formulations. Further, characterization of the bioactive metabolites responsible for biocontrol was performed. A new microbial formulation, WDG, was developed in the present study with talcum powder (substrate), alginic acid (dispersing agent) and acacia gum (wetting agent) (suspensibility 82.23%; wetting time 2.5 min; dispersion time 10.08 min) that fulfilled the guidelines of Collaborative International Pesticides Analytical Council (CIPAC). In planta study demonstrated that WDG of B. subtilis showed maximum reduction in disease incidence (48%) followed by talc formulation of B. subtilis (44%) and WDG of T. harzianum (42%) with profound effect on plant growth promotion. B. subtilis and T. harzianum demonstrated protease (929 and 846 U ml−1 min−1), chitinase (33.69 and 154 U ml−1 min−1), and β-1,3-glucanase (12.69 and 21.47 U ml−1 min−1) activities. Culture filtrates of B. subtilis and T. harzianum exhibited significant inhibition against mycelial growth of pathogen. The compounds present in the culture filtrates were identified with GC–MS as fatty acids, alkanes, phenols, benzene, pyran derivatives etc. The major non-volatile compounds in bioactive antifungal fraction were identified as derivatives of morpholine and piperdine for T. harzianum and B. subtilis, respectively. The findings propose a multivariate biocontrol mechanism against phytopathogen by production of hydrolytic enzymes, volatile and non-volatile compounds, together with development of an efficient next-generation formulation.